Group B Streptococcus Brain Abscess in a Neonate with Bilateral Otorrhea - Spencer, Emily E.; Nostrand, Sarah Van; Arya, Shreyas (American Journal of Perinatology Reports, 2024)
Introduction Group B streptococcus (GBS) is the leading cause of bacterial sepsis and meningitis in neonates worldwide, but brain abscess secondary to GBS is extremely rare. While temporal brain abscesses have been described as a sequelae of otogenic infections in children and adults, such a presentation has not been described in neonates.Case Description An 8-day-old female infant presented with a fever and irritability along with bilateral purulent otorrhea. Maternal GBS screening was negative, but the delivery was complicated by chorioamnionitis. Workup revealed neutrophilic pleocytosis in the cerebrospinal fluid and culture of the ear drainage was positive for GBS. Magnetic resonance imaging showed a circular lesion with rim enhancement within the left temporal lobe concerning for an abscess. The infant was treated with 14 days of intravenous vancomycin, cefepime, and metronidazole followed by 10 weeks of intravenous ampicillin. The hospital course was complicated by seizures and obstructive hydrocephalus requiring multiple neurosurgical interventions.Conclusion Brain abscess can occur as a sequela of GBS meningitis in neonates, but they are rare. Otogenic infections require prompt evaluation and treatment as they can progress to serious central nervous infections in neonates.
Keywords: group B streptococcus; neonate; brain abscess; meningitis; otorrhea